STUDY OF VERNACULAR HOUSE ENDURANCE IN SOUTH SULAWESI TO EARTHQUAKE AS A RESULT OF QUALITY CHANGE IN STRUCTURE MATERIAL - Sudarman Sudarman; Muhammad Attar (Universitas Mercu Buana, 2020)
Rumah Vernakular dengan material kayu merupakan rumah mayoritas masyarakat di Indonesia termasuk Sulawesi Selatan, dimana rumah-rumah ini telah terbukti dapat tahan terhadap gempa yang sering terjadi di Indonesia karena dibangun dengan materika kayu kelas I. Akan tetapi belakangan ini keterbatasan kayu kelas I seperti Kayu Ulin yang merupakan katerial struktur pada kebanyakan rumah vernacular di Sulawesi Selatan mendorong masyarakat untun mengganti kayu kelas I dengan kayu kelas II dan III sebagai material struktur yang digunakan seperti Kayu Kumea Batu. Hasil Penelitian dengan menggunakn metode simulasi menggunakan SAP 2000 dapat disimpulkan bahwa metode konstruksi yang ada sekarang dengan adanyanpenurunan kualitas material struktur tidak mampu menahan gaya lateral yang ditimbulkan oleh beban gempa terutama untuk gempa kategori kuat. Vernacular house with the wooden material is the majority house of Indonesia society expecially in South Sulawesi. These houses are proven could resistant to earthquake in Indonesia because is built with the wood of the best quality like “Ulin Wood”. However limitations of wood with the best quality like “Ulin Wood” that be used to structural material push the society to replace with the low quality (Wood Grade II and Wood Grade III) wood. The result of the research with the simulation method (SAP 2000) could be conclusion the construction method apllied now with decrease of quality structure material unable to resist of seismic force expecialy for strong earthquake it could seen that the displacement that occurs on the x-axis of the 2nd floor and the y-axis on the 1st and 2nd floors is greater than the permit of displacement that the building structure does not suitable performance standards according to the SNI-1726-2002 equation in the soft soil conditions.